Pharmacological potential of Bidens pilosa L. and determination of bioactive compounds using UHPLC-QqQLIT-MS/MS and GC/MS - Garima Singh; Ajit Kumar Passsari; Pratibha Singh; Vincent Vineeth Leo; Sarathbabu Subbarayan; Brijesh Kumar; Bhim Pratap Singh; Hauzel lalhlenmawia; Nachimuthu Senthil Kumar (BMC, 2017)
Abstract Background Research of natural products from traditionally used medicinal plants to fight against the human ailments is fetching attention of researchers worldwide. Bidens pilosa Linn. var. Radiata (Asteraceae) is well known for its folkloric medicinal use against various diseases from many decades. Mizoram, North East India, has high plant diversity and the use of this plant as herbal medicine is deep rooted in the local tribes. The present study was executed to understand the pharmacological potential of B. pilosa leaves extract. Methods The antimicrobial potential was determined using agar well diffusion and broth microdilution method against bacterial and yeast pathogens. Cytotoxicity was evaluated using MTT and apoptotic DNA fragmentation assays. Further, the antioxidant ability of the extract was analysed using DPPH and ABTS free radical scavenging assay. Mosquitocidal activity was evaluated against third in-star larvae of C. quinquefasciatus using dose response and time response larvicidal bioassay. Additionally, the major phenolic and volatile compounds were determined using UHPLC-QqQLIT-MS/MS and GC/MS respectively. Results We found that the extract showed highest antimicrobial activity against E. coli (MIC 80 μg/mL and IC50 110.04 μg/mL) and showed significant cytotoxicity against human epidermoid carcinoma (KB-3-1) cells with IC50 values of 99.56 μg/mL among the tested cancer cell lines. The IC50 values for scavenging DPPH and ABTS was 80.45 μg/mL and 171.6 μg/mL respectively. The extract also showed the high phenolics (72 μg GAE/mg extract) and flavonoids (123.3 μg Quercetin /mg extract). Lastly, five bioactive and six volatile compounds were detected using UHPLC-QqQLIT-MS/MS and GC-MS respectively which may be responsible for the plant's bioactivities. An anticancerous compound, Paclitaxel was detected and quantified for the first time from B. pilosa leaves extract, which further showed the anticancerous potential of the tested extract. Conclusion On the basis of the present investigation, we propose that the leaf extract of B. pilosa might be a good candidate for the search of efficient environment friendly natural bioactive agent and pharmaceutically important compounds.